Symbolic Interactionism of The Main Character in The “Noah” Movie: A Sociolinguistic Analysis - Miftahurrahmah Ria, Nurul; Mustikawati, Yunitari; Sahril, Sahril (State University of Makassar, 2025)
This research is entitled